Associations between pancreatic expression quantitative traits and risk of pancreatic ductal adenocarcinoma. (3rd July 2021) - Pistoni, Laura; Gentiluomo, Manuel; Lu, Ye; López de Maturana, Evangelina; Hlavac, Viktor; Vanella, Giuseppe; Darvasi, Erika; Milanetto, Anna Caterina; Oliverius, Martin; Vashist, Yogesh; Di Leo, Milena; Mohelnikova-Duchonova, Beatrice; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is among the most lethal cancers. Its poor prognosis is predominantly due to the fact that most patients remain asymptomatic until the disease reaches an advanced stage, alongside the lack of early markers and screening strategies. A better understanding of PDAC risk factors is essential for the identification of groups at high risk in the population. Genome-wide association studies (GWAS) have been a powerful tool for detecting genetic variants associated with complex traits, including pancreatic cancer. By exploiting functional and GWAS data, we investigated the associations between polymorphisms affecting gene function in the pancreas (expression quantitative trait loci, eQTLs) and PDAC risk. In a two-phase approach, we analysed 13 713 PDAC cases and 43 784 controls and identified a genome-wide significant association between the A allele of the rs2035875 polymorphism and increased PDAC risk ( P = 7.14 × 10 −10 ). This allele is known to be associated with increased expression in the pancreas of the keratin genes KRT8 and KRT18, whose increased levels have been reported to correlate with various tumour cell characteristics. Additionally, the A allele of the rs789744 variant was associated with decreased risk of developing PDAC ( P = 3.56 × 10 –6 ). This single nucleotide polymorphism is situated in the SRGAP1 gene and the A allele is associated with higher expression of the gene, which in turn inactivates the cyclin-dependent protein 42 ( CDC42 ) gene expression, thus decreasing the risk of PDAC. In conclusion, we present here a functional-based novel PDAC risk locus and an additional strong candidate supported by significant associations and plausible biological mechanisms. Abstract : For the first time, all pancreatic expression quantitative trait loci were analysed in relation to pancreatic cancer risk, in an association study with over 20 000 individuals. We identified a novel variant in the SRGAP1 gene associated with pancreatic cancer risk.